Platformisation - Thomas Poell; David Nieborg; José van Dijck (Internet Policy Review, 2019)
This article contextualises, defines, and operationalises the concept of platformisation. Drawing insights from different scholarly perspectives on platforms—software studies, critical political economy, business studies, and cultural studies—it develops a comprehensive approach to this process. Platformisation is defined as the penetration of infrastructures, economic processes and governmental frameworks of digital platforms in different economic sectors and spheres of life, as well as the reorganisation of cultural practices and imaginations around these platforms. Using app stores as an example, we show how this definition can be employed in research.
Keywords: 300; Platforms; Platformisation; Datafication; Multi-sided markets; Political economy; Governance